Small differences in seasonal and thermal niches influence elevational limits of native and invasive Balsams. (November 2015) - Laube, Julia; Sparks, Tim H.; Bässler, Claus; Menzel, Annette
Abstract: Recent studies suggest that invasive plant species have colonised mountains to previously unobserved elevations, possibly due to ongoing climate change. Thus, they might pose new threats to high-elevation ecosystems, which are often of high conservation value. Current range predictions are primarily based on climate niche models, however many other factors might also contribute to the species' distribution. We studied the species-specific elevational limits of one native ( Impatiens noli-tangere ) and two invasive balsams ( Impatiens glandulifera and Impatiens parviflora ) on a mid-mountain range in Germany. We used a combination of trait measurements and a field experiment to assess the relative importance of temperature, trait adaptations, and biotic interactions on elevational limits. Results indicate that concurrent seedling emergence, low frost resistance and, for I. glandulifera, late flowering, are important contributors to elevational limits. Because of a lack of seed bank persistence, erratic spring and autumn frost events coinciding with the plants' annual life-cycles will likely influence the upper limits of the invasive species. The abundance of the species seems to be further limited by herbivory, mainly by molluscs. Given that a highly nuanced interaction between phenological development and erratic frost events are important for range limits, predictions based solely on mean climatic values, such as temperature, are unlikely to accurately predict future invasion limits. Our results indicate that occasional occurrences of the species do not necessarily call for eradication actions, that management efforts might be most effective at intermediate elevations, and that any measure encouraging terrestrial molluscs will help to maintain biotic resistance. Highlights: We investigate the drivers of upper range limits of invasive and native Balsams. A unique set of elevational trait measurements and field experiments is used. Low frost resistance and late reproduction trigger elevation limits. Due to erratic frost events, an upward shift with climate change seems unlikely. Management should concentrate on midelevations, and include measures for molluscs.